Трав’янистий покрив гірсько-горбкуватого ландшафтного району дендропарку “Тростянець” - Nesterenko, V.P.; Ilyenko, A.A.; Medvedev, V.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
The floristic and phyto-coenotic description of the herbaceous vegetation of mountain undulating area of dendropark Trostyanets are given.